Bacterial Degraders of Coexisting Dichloromethane, Benzene, and Toluene, Identified by Stable-Isotope Probing - Yoshikawa, Miho (Water Air Soil Pollut, 2017)
Most bioremediation studies on volatile organic compounds (VOCs) have focused on a single contaminant or its derived compounds and degraders have been identified under single contaminant conditions. Bioremediation of multiple contaminants remains a challenging issue. To identify a bacterial consortium that degrades multiple VOCs (dichloromethane (DCM), benzene, and toluene), we applied DNA-stable isotope probing. For individual tests, we combined a (13)C-labeled VOC with other two unlabeled VOCs, and prepared three unlabeled VOCs as a reference. Over 11 days, DNA was periodically extracted from the consortia, and the bacterial community was evaluated by next-generation sequencing of bacterial 16S rRNA gene amplicons. Density gradient fractions of the DNA extracts were amplified by universal bacterial primers for the 16S rRNA gene sequences, and the amplicons were analyzed by terminal restriction fragment length polymorphism (T-RFLP) using restriction enzymes: HhaI and MspI. The T-RFLP fragments were identified by 16S rRNA gene cloning and sequencing. Under all test conditions, the consortia were dominated by Rhodanobacter, Bradyrhizobium/Afipia, Rhizobium, and Hyphomicrobium. DNA derived from Hyphomicrobium and Propioniferax shifted toward heavier fractions under the condition added with (13)C-DCM and (13)C-benzene, respectively, compared with the reference, but no shifts were induced by (13)C-toluene addition. This implies that Hyphomicrobium and Propioniferax were the main DCM and benzene degraders, respectively, under the coexisting condition. The known benzene degrader Pseudomonas sp. was present but not actively involved in the degradation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11270-017-3604-1) contains supplementary material, which is available to authorized users.